In View of Psychology, What Are the Precipitating Factors for Purchasing Luxury Brand Commodities in Baku and Seoul? Primary Cross-Cultural Research Study - Gasimzade, Fatima (Digital Repository of Theses, 2024)
Background: The Asian luxury goods market is one of the largest luxury goods consumers, and the number of people seeking to acquire luxury goods from reputable brands is growing predominantly in Asian countries. Many people tend to appreciate and admire luxury fashion since it is considered the embodiment of beauty that is all about sophistication and serenity. Nevertheless, when and why did humans start wearing clothes? Was it because they felt cold, or they wanted to cover up their naked bodies? A cross-cultural research study was carried out in Azerbaijan and South Korea to find answers to these questions since there was no prior research study on this topic. Aim: Today, the reason for wearing clothes has gone far beyond the basics, especially with regard to luxury fashion, since it is a form of self-expression that exemplifies eople’s discrete tastes. However, what are the precipitating factors for purchasing luxury brand commodities in terms of psychology? Methods: A cross-cultural research study was conducted in Baku and Seoul to examine this topic more profoundly with regard to psychology. Participants were selected using the purposive sampling method. There were 24 participants in total. The ages of the participants ranged from 24 to 78. In each city, there were two groups of participants: 7 participants in the client group and 5 participants in the non-client group of luxury brands. To collect data, a semi-structured interview was conducted. To analyse gathered data thematic analysis was used. Results: According to the results, factors influencing people’s purchasing behaviour of luxury fashion goods in Baku and Seoul are the fulfilment of needs and contentment, hedonism, psychological well-being, and culture. It was also found that people do not buy luxury predominantly because of their socio-economic background, negative attitudes towards luxury, and cultural impact. Conclusion: Thus, further research should be conducted in order to provide some insights into the contradictory topic of luxury and its influence on people. Keywords: Luxury fashion brands, luxury consumption factors, Baku, Seoul